Effects of Al doping on the structural, electrical, and optical properties of rock-salt ZnCdO thin films grown by molecular beam epitaxy. (April 2022) - Jang, HyoChang; Saito, Katsuhiko; Guo, Qixin; Yu, Kin Man; Tanaka, Tooru
Abstract: The effects of Al doping on the structural, electrical, and optical properties of rock-salt (RS)-Zn1- x Cd x O (ZnCdO) thin films were investigated. The films were grown by molecular beam epitaxy under various Al cell temperatures. Reflection high-energy electron diffraction and compositional analyses indicated that single-crystal RS-ZnCdO ( x  ≈ 0.83) layers were obtained with up to 7.8% Al incorporation. The electron concentration in the thin films increased with increasing Al cell temperature and was 1.5 × 10 21  cm −3  at ∼7.8% Al. Al-doped RS- and wurtzite (WZ)-ZnCdO thin films with various Cd concentrations were grown under the same Al cell temperatures. The ZnCdO films had an electron concentration of 10 21  cm −3 for Cd content x ranging over 0.27–1.0, regardless of the crystal structure. Al-doped RS-ZnCdO films had a 3.45-eV optical band gap at x  = 0.7 because of the high electron concentration that led to a Burstein-Moss shift. This was the highest-energy optical band gap reported for RS-ZnCdO. Therefore, Al doping was very effective in expanding the optical band gap, as well as increasing the RS-ZnCdO electrical conductivity, making the films suitable as transparent conductors for full-spectrum solar cells. Highlights: Al-doped Zn1- x Cd x O thin films were grown on MgO substrate by molecular beam epitaxy. Effect of Al doping on the structural, electrical, and optical properties of RS-ZnCdO thin films was investigated systematically. A large optical band gap of 3.45 eV was achieved in RS-ZnCdO thin film with x ≈ 0.7 with a low resistivity of ∼1 × 10 −4  Ω-cm.